(3CQLhRI aj GdWHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdQFjS CHh Ydi GdMSjf SYjO Hf YHO Gddg Hf SjfG (B_ (3QMeg Gddg (B- (3deG LQJ YGOI GdMceGA haVdGA GdbOeGA s
(3BNQgG (B:s
(3abO aQZJ ef LejY GdYed hGdBf CbWY Hbhd eced s
(3GdfSNI HgG MhGTs
(3eUOQI HebOeI ai GdChRGf GdTYQs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs